Morpho-physiological and yield attributes of boro rice varieties as influenced by different nitrogen sources - Parvin Akter Bithy (Research in Agriculture Livestock and Fisheries, 2023)
The present study was carried out at the Research Field of Sher-e-Bangla Agricultural University (SAU), Dhaka during Boro season, 2021-2022 to discover the best nitrogen source for enhancing Boro rice grain production. The experiment consisted of two factors: A) Three varieties: BRRI dhan29 (V1), BRRI dhan58 (V2), and Heera (V3). B) Four nitrogen sources: no nitrogen (T1), BRRI-recommended prilled urea (T2), recommended dose of mixed NPK (T3), and BARC-recommended USG (T4). The experiment was laid out in split plot design with three replications where main plot was for nitrogen source and subplot was for variety. USG treatment resulted in the highest grain production (8.6 t/ha) and the lowest percentage of spikelet sterility of any nitrogen source tested. Except for harvest index, all of the examined characteristics differed considerably between types. This is mostly due to BRRI dhan29 having the maximum number of full grains (98.8/panicale) and a significantly lower degree of spikelet sterility (7.3%). Among the interaction effects, the combination of the USG application with BRRI dhan29 showed the greatest performance in terms of delivering the maximum grain production (9.3 t/ha) by significantly reducing spikelet sterility. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 175-182